2000
DOI: 10.1070/qe2000v030n04abeh001713
|View full text |Cite
|
Sign up to set email alerts
|

The spectroscopy and lasing of monoclinic Tm:KY(WO4)2crystals

Abstract: The principal spectroscopic and lasing characteristics of a Tm(15%) : KY(WO 4 ) 2 crystal were investigated. The transition cross sections, the luminescence quantum yield, and the lifetime and the nonlinear depopulation coefficient of the upper active state were also determined. The slope efficiency of lasing at the 1950 nm wavelength was 45%. The feasibility of tuning in the spectral range 18501 950 nm was demonstrated in principle. S N Bagaev, S M Vatnik, A P Maiorov, D V Plakushchev Institute of Laser Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…The first demonstration of Tm lasing on the F H transition in monoclinic double tungstates was realized in 1997 with Xe-flash lamp pumping where Tm:KY(WO ) (Tm:KYW) and Tm:KGd(WO ) (Tm:KGdW) rods sensitized with Er and Yb operated at cryogenic temperatures and wavelengths of 1920 and 1930 nm, respectively [14]. Soon afterwards continuous-wave (CW) room-temperature operation of highly doped (15%) Tm:KYW was demonstrated with longitudinal Ti:sapphire laser pumping near 800 nm [15]. Codoping of Tm:KYW with Yb for InGaAs diode pumping at 980 nm with subsequent excitation transfer was studied in [16] but laser experiments revealed no practical advantages as compared to direct 800 nm pumping by AlGaAs diodes [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first demonstration of Tm lasing on the F H transition in monoclinic double tungstates was realized in 1997 with Xe-flash lamp pumping where Tm:KY(WO ) (Tm:KYW) and Tm:KGd(WO ) (Tm:KGdW) rods sensitized with Er and Yb operated at cryogenic temperatures and wavelengths of 1920 and 1930 nm, respectively [14]. Soon afterwards continuous-wave (CW) room-temperature operation of highly doped (15%) Tm:KYW was demonstrated with longitudinal Ti:sapphire laser pumping near 800 nm [15]. Codoping of Tm:KYW with Yb for InGaAs diode pumping at 980 nm with subsequent excitation transfer was studied in [16] but laser experiments revealed no practical advantages as compared to direct 800 nm pumping by AlGaAs diodes [21].…”
Section: Introductionmentioning
confidence: 99%
“…We note that the combination of broad fluorescence line, large emission cross section and relatively low upper level lifetime (Table I) is an unique advantage for future experiments on passive mode-locking with such lasers and the generation of femtosecond pulses by an all-solid state laser system tunable in the 2-m spectral range. Tm-doped double tungstates have an absorption line centered at 800-802 nm [15], [25] with a broader longwave wing very suitable for diode pumping. The first demonstration of Tm lasing on the F H transition in monoclinic double tungstates was realized in 1997 with Xe-flash lamp pumping where Tm:KY(WO ) (Tm:KYW) and Tm:KGd(WO ) (Tm:KGdW) rods sensitized with Er and Yb operated at cryogenic temperatures and wavelengths of 1920 and 1930 nm, respectively [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.6-2.0 m lasers are safe to human eyes and thus are also widely used in medicine. Most solid-state 1.6-2.0 m laser operations are based on transition 3 F 4 → 3 H 6 in thulium ions and the performance of the thulium ions in a number of solid-state host has been widely studied and laser operation has been successfully realized [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…% Tm 3+ :KY͑WO 4 ͒ 2 was demonstrated with longitudinal Ti:sapphire laser pumping near 800 nm. 5 They found that the thulium concentration must be high enough to ensure efficient pumping, but low enough to minimize concentration quenching effects due to cross-relaxation-type ͑ 3 H 4 + 3 H 6 → 3 F 4 + 3 F 4 ͒ and nonradiative energy transfer between active ions. In 2002, Yb 3+ , Tm 3+ :KY͑WO 4 ͒ 2 was studied for InGaAs diode pumping at 980 nm with subsequent excitation transfer from Yb 3+ to Tm 3+ ions at several dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%